The RH5-CyRPA-Ripr Complex as a Malaria Vaccine Target. Issue 6 (June 2020) - Ragotte, Robert J.; Higgins, Matthew K.; Draper, Simon J.
Abstract : Despite ongoing efforts, a highly effective vaccine against Plasmodium falciparum remains elusive. Vaccines targeting the pre-erythrocytic stages of the P. falciparum life cycle are the most advanced to date, affording moderate levels of efficacy in field trials. However, the discovery that the members of the merozoite PfRH5-PfCyRPA-PfRipr (RCR) complex are capable of inducing strain-transcendent neutralizing antibodies has renewed enthusiasm for the possibility of preventing disease by targeting the parasite during the blood stage of infection. With Phase I/II clinical trials now underway using first-generation vaccines against PfRH5, and more on the horizon for PfCyRPA and PfRipr, this review explores the rationale and future potential of the RCR complex as a P. falciparum vaccine target. Highlights: The antigens PfRH5, PfCyRPA, and PfRipr can induce strain-transcendent neutralizing antibodies, and all three targets are essential and highly conserved. PfRH5, PfCyRPA, and PfRipr form a stable complex (RCR) that is involved in the induction of an erythrocytic calcium spike during merozoite invasion. Passive transfer of anti-CyRPA and anti-PfRH5 antibodies can protect against blood-stage P. falciparum in animal models. Structural studies have mapped out the first known critical inhibitory epitopes on PfRH5 and PfCyRPA which can be used for next-generation vaccine design. Early results from the first PfRH5 vaccine clinical trials have been reported with more anticipated soon, which will help guide the development of RCR-based vaccines.